2022
DOI: 10.1108/mbe-01-2022-0020
|View full text |Cite
|
Sign up to set email alerts
|

Exploring intellectual capital disclosure and its determinants in knowledge-based institutions: empirical evidence from international universities

Abstract: Purpose This study aims to add empirical evidence to the intellectual capital (IC) literature by enhancing understanding of voluntary online IC disclosure (ICD) practices in knowledge-based institutions such as universities from an international standpoint. The ultimate purpose of this study is to examine how different variables related to size, internet visibility and certain corporate governance attributes (i.e. board size and board gender diversity) affect the extent to which universities from different wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…From an empirical point of view, to the best of our knowledge, there are no studies that have examined the impact of the Internet visibility of hospitals on the amount of information disclosed. However, in other contexts such as universities, previous studies have found a positive impact of the Internet visibility on the amount of information disclosed (Manes Rossi et al, 2018;Vitolla et al, 2023).…”
Section: Hypotheses Developmentmentioning
confidence: 97%
“…From an empirical point of view, to the best of our knowledge, there are no studies that have examined the impact of the Internet visibility of hospitals on the amount of information disclosed. However, in other contexts such as universities, previous studies have found a positive impact of the Internet visibility on the amount of information disclosed (Manes Rossi et al, 2018;Vitolla et al, 2023).…”
Section: Hypotheses Developmentmentioning
confidence: 97%